2021
DOI: 10.1017/jfm.2021.867
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer from small spheroids suspended in a turbulent fluid

Abstract: By coupling direct numerical simulation of homogeneous isotropic turbulence with a localised solution of the convection–diffusion equation, we model the rate of transfer of a solute (mass transfer) from the surface of small, neutrally buoyant, axisymmetric, ellipsoidal particles (spheroids) in dilute suspension within a turbulent fluid at large Péclet number, $\textit {Pe}$ . We observe that, at $\textit {Pe} = O(10)$ , the average transfer rate for prolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Batchelor then argues that at large turbulent Péclet number Pe = a 2 τ η /D = Re 3/2 Sc, due to the convection-suppression effect (Batchelor 1979), particle motion due to slip has a negligible effect on the mass transfer rate because the particle rotates isotropically. This convection-suppression mechanism has recently been confirmed in turbulent flows to suppress convective mass transfer by velocity fluctuations occurring on a time scale more rapid than τ η Pe 1/3 (Lawson & Ganapathisubramani 2021). In the limit of Pe → ∞, Batchelor concluded that for small spherical particles, the only component of the relative flow field which is persistent upon averaging over time in the particle reference frame is an axisymmetric strain, whose magnitude scales with 1/τ η .…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…Batchelor then argues that at large turbulent Péclet number Pe = a 2 τ η /D = Re 3/2 Sc, due to the convection-suppression effect (Batchelor 1979), particle motion due to slip has a negligible effect on the mass transfer rate because the particle rotates isotropically. This convection-suppression mechanism has recently been confirmed in turbulent flows to suppress convective mass transfer by velocity fluctuations occurring on a time scale more rapid than τ η Pe 1/3 (Lawson & Ganapathisubramani 2021). In the limit of Pe → ∞, Batchelor concluded that for small spherical particles, the only component of the relative flow field which is persistent upon averaging over time in the particle reference frame is an axisymmetric strain, whose magnitude scales with 1/τ η .…”
Section: Introductionmentioning
confidence: 72%
“…Therefore, in Batchelor's analysis, the sinking ratio does not appear as a control parameter. However, for neutrally buoyant spheroids, we have empirically shown shown that at large but finite Pe, the solution of (2.8) is best approximated by (2.12) when the time scale is chosen τ f ∼ Pe 1/3 (Lawson & Ganapathisubramani 2021). Under this hypothesis, it is therefore still possible for slip to contribute to the convective mass transfer, because v 0 does not vanish when averaging over a finite time interval.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
See 3 more Smart Citations